Poperties of polyethersulphone ultrafiltration membranes modified with polyethylene glycols - Méndez, Mercedes Liliana (2013)
Polyethersulfone ultrafiltration membranes have been prepared using polyethylene glycols (PEGs) of 400, 1000, and 10,000 gmol, as additive with dimethylacetamide as solvent. Infrared analysis proves that PEG leaves almost completely the surface of the membranes after 24 h of water immersion. Scanning electron microscopy, contact angle, and liquid–liquid displacement porometry have been used to characterize the membrane morphology, surface hydrophilicity and porous structure. The relative flux reduction factor, flux, retention—of PEG (20,000 and 35,000 g/mol) and bovine serum albumin (67,000 g/mol)—and pure water permeability have been measured for the membranes. Results show that the addition of PEG increases slightly hydrophilicity and decreases pore size and narrows the corresponding pore size distribution while thickening the skin layer, in spite of the fast disappearance of the added PEG form the membrane surface. The resulting flux and pure water permeability are higher when middle size PEGs are added but decrease again when very high molecular weight (MW) PEGs are added. Retention decreases initially for increasing MWs of PEG although for very long PEG chains (MW of 10,000 g/mol) retention increases again. After filtration, the membranes with PEG added showed a lower relative flux reduction that decreases for increasing MW of the added PEGs.